2017
DOI: 10.1097/coh.0000000000000365
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvants

Abstract: Purpose of review The development and availability of new generation adjuvants beyond aluminum and emulsion formulations, together with a deeper understanding of the mechanistic role of adjuvant formulations in stimulating innate immunity, offer opportunities to improve candidate vaccine designs intended to protect against HIV-1 acquisition. Recent findings Currently, major efforts in vaccine development focus on improving prime-boost vaccine regimens to enhance efficacy beyond 31% observed in the RV144 phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In an attempt to attain more and more protective responses and to also overcome potential side effects associated with highly immune-stimulatory adjuvants, mixed adjuvant regimens have gained in popularity. Recently, a number of excellent reviews have been published concerning adjuvants for HIV-1 vaccines ( 93 , 94 ), so we will discuss only a few of the more common adjuvants below, some of which are detailed in Table 3 .…”
Section: Strategies To Increase Immunogenicity Of Nano-vaccinesmentioning
confidence: 99%
“…In an attempt to attain more and more protective responses and to also overcome potential side effects associated with highly immune-stimulatory adjuvants, mixed adjuvant regimens have gained in popularity. Recently, a number of excellent reviews have been published concerning adjuvants for HIV-1 vaccines ( 93 , 94 ), so we will discuss only a few of the more common adjuvants below, some of which are detailed in Table 3 .…”
Section: Strategies To Increase Immunogenicity Of Nano-vaccinesmentioning
confidence: 99%
“…Furthermore, preliminary results showed that gCTB's DC-SIGN-binding affinity could be significantly enhanced when the protein was produced under kifunensine treatment (Hamorsky et al, 2015 ), providing a basis for the present study and for the development of novel C-type lectin receptor-targeting vaccines. HIV-1 gp120, on the other hand, is a primary target of broadly neutralizing antibodies, thus constituting an important component of experimental HIV-1 vaccines (Zhou et al, 2007 ; Karlsson Hedestam et al, 2017 ; McElrath, 2017 ). Our results in the present work demonstrate that recombinant glycoproteins transiently expressed in N. benthamiana have predominantly Man9 HMGs upon hydroponically treating the plant with kifunensine after vector inoculation, providing a new method for the efficient production of highly mannosylated antigens for vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…While it would have been exciting to find that we could both inhibit viral transmission and overcome the tolerant phenotype LC taken on after exposure to HPV virions ( 61 , 62 ), it appears as though tolerogenic interactions by HPV viral aggregates are maintained. Future studies looking to use RTD-1 mediated viral aggregates as an attempt to generate antiviral responses in APC populations other than LC could consider the addition of adjuvants that enhance humoral responses to bolster the production of neutralizing antibodies against the viral vector ( 63 ).…”
Section: Discussionmentioning
confidence: 99%